Tetfund Interventions On Administrative Functions and Academic Staff Development in The Management of Federal Universities in South East, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigated TETFund interventions on administrative functions and academic staff development in the management of Federal Universities in South East, Nigeria. Two research questions and two hypotheses guided the study. This study adopted a descriptive survey design. The population of this study comprised all the 231 staff from the five (5) federal universities in South East, Nigeria. This consisted of 16 staff in TETFund offices and 215 Heads of Departments in the five federal universities in South East, Nigeria. The entire population comprising 231 TETFund staff and Heads of Departments in the five federal universities in South East, Nigeria were used as the study sample purposively in this research. The instrument used in this study was questionnaire titled “TETFund Interventions on Administrative Functions and Academic Staff Development in the Management of Federal Universities’ Questionnaire (TIAFASDMFUQ). The instrument was validated and the reliability of the instrument was established using Cronbach alpha to determine the internal consistency yielded an overall reliability index of 0.81. In analyzing the data, mean scores and standard deviation were used to answer the research questions. The t-test was used to test the hypotheses at a 0.05 level of significance. The findings revealed that, TETFund intervention had significant impact on the administrative functions for the management of federal universities in South East, Nigeria. TETFund intervention had significant impact on academic staff development for proper management of federal universities in South East, Nigeria. TETFund intervention had significant impact on research developments for the management of federal universities in South East, Nigeria. Based on the findings, the researcher recommended among others that, Government through TETFund intervention should ensure that funds released for smooth running of administrative functions in federal universities in South East, Nigeria. TETFund should intervene in providing grants for academic staff development for conference participation (International and National), and publications in federal universities in South East, Nigeria.